Pengaruh Edukasi oleh Apoteker dengan Metode Brief Counseling terhadap Pengetahuan, Kepatuhan dan Glukosa Darah Pasien DM Tipe 2 di Puskesmas Kabupaten Pemalang - Irrene Wulan Syafitri; Nanang Munif Yasin; Ika Puspita Sari (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
The problem currently encountered by Diabetes Mellitus (DM) patients is a decrease interaction in routine activities carried out at first-level health facilities due to the Covid-19 pandemic. This study is to determine the effect of education by pharmacists with media brief counseling on the knowledge, compliance, and clinical outcomes of DM patients. This type of research is a quasi-experimental method with a pretest and posttest design with the control group. This study was conducted prospectively to analyze the effect of brief counseling-based pharmaceutical services by pharmacists on the level of knowledge measured using the Diabetic Knowledge Questionnaire-24 (DKQ-24), the level of compliance was measured using the Morisky Green Levine Scale (MGLS) questionnaire, and the clinical outcomes of type 2 DM patients at the Puskesmas in Pemalang Regency from October to November 2021. The analysis to measure the bivariate differences in one group used the paired sample t-test, and the bivariate differences between groups were measured using the independent sample t-test. This study consisted of 32 patients in each control and intervention groups. The descriptive analysis of this study showed no differences in data on patient characteristics in the control and intervention groups (p>0.05). The results showed that there was an increase in patient knowledge from 12,66±2,43 to 21,75±1,81 (p=0,000) and an increase in patient compliance from 2,03±0,96 to 0,25±0,51 (p=0,000) after being given brief counseling. The clinical outcomes of DM patients showed that there was an improvement from 177,63±82,4 to 159±58,1 (p=0,002). Based on these results, it can be concluded that there is an effect of education by a pharmacist using the brief counseling method on the level of knowledge, compliance, and clinical outcome of type 2 DM patients.